Teletrabalho e produtividade : há influência? : um estudo à luz do Programa de Gestão e Desempenho (PGD) nas Superintendências do Patrimônio da União - Santana, Deise Maisa Ribeiro de (2023)
From the technological revolution that allowed an increasingly comprehensive connectivity, and enabled new ways of performing work, the purpose of this research is to analyze what influence telework has on the productivity of teleworkers. The literature commonly indicates productivity gain as one of the main benefits perceived by teleworkers, but also indicates that, depending on the circumstances involved, the same productivity can be negatively affected. This is a research of quantitative approach and descriptive and exploratory character, whose method used to perform the existing analysis between the constructs telework and productivity was the multivariate analysis technique called Structural Equation Modeling (SEM), based on Partial Least Squares (PLS), in which a path diagram or initial model was proposed, and was carried out in the context of the Management and Performance Program (PGD), with federal employees of the units of the Superintendencies of the Patrimony of the Union (SPU). Based on the bibliographic sources that supported the study, ICT and remote work were defined as elements that form telework (independent variable). As for productivity, it was based on the IAPT scale, validated by Menezes and Xavier (2018), for the construction of the second construct (dependent variable). After the first stage of analysis, with the evaluation of the measurement model, it was found that the formative elements and the indicators of telework had the ability to measure the construct satisfactorily, however, as for productivity, there was a need to adjust the model. In the second stage, the structural model was evaluated to verify the relationship between the constructs. Three hypotheses were proposed to analyze the relationship between telework and productivity, and hypothesis H3 was confirmed, indicating that telework explains 37.9% of the variance in teleworkers' productivity. It was concluded, from the test of the hypotheses, that the telework performed by the federal employees of the PGD directly and positively influences the productivity of the teleworkers of the Superintendencies of the Patrimony of the Union.